MET Inhibitors in Small Cell Lung Cancer: From the Bench to the Bedside - Hardy-Werbin, Max (Cancers (Basel), 2019)
Small cell lung cancer (SCLC) is the most aggressive type of lung cancer. The different systemic treatment approaches attempted in the last 35 years have not improved overall survival in the advanced stage. Targeted therapies assessed in clinical trials have failed to show efficacy against SCLC. Within the potentially interesting targets, the hepatocyte growth factor (HGF)/mesenchymal-epithelial transition (MET) pathway activation is associated with worse survival and chemoresistance in SCLC. Preclinical data suggest that the inhibition of the MET pathway can revert chemoresistance and prevent tumor growth. Recently, immunotherapy has shown modest but relevant activity in SCLC. Interestingly, MET modulation seems to be involved in increasing the efficacy of standard checkpoint inhibitors. Here, we review the preclinical and clinical data of MET inhibition in SCLC, and the role of this pathway in the immune response.